Struktur modal dan profitabilitas: Peran ESG skor sebagai pemoderasi - Lazarus Sinaga (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study examines the impact of the Debt-to-Equity Ratio (DER) on Return on Assets (ROA), taking into account Environmental, Social, and Governance (ESG) factors as a moderating variable. The study used a sample of 30 multi-sector companies listed on the Indonesia Stock Exchange for the period from 2020 to 2023, purposively selected based on the availability of sustainability reports. Moderated Regression Analysis (MRA) was used for data analysis using JAMOVI 2.6 software. The study's findings revealed that DER had a negative and significant effect on ROA, indicating that increased leverage negatively impacts corporate profitability. An interesting finding is the role of ESG as a negative moderator, significantly weakening the negative relationship between DER and ROA. Hence, implementing ESG practices can mitigate the negative impact of debt use on corporate financial performance. Public interest statements This study makes a significant contribution to the corporate finance literature by demonstrating that a commitment to ESG not only benefits sustainability but also serves as a financial risk mitigation mechanism. These findings have practical implications for corporate management in formulating capital structure policies that take into account sustainability.